Flutuações agregadas e setoriais no ICMS setorial do Ceará: uma abordagem a partir do modelo de fatores dinâmicos - Perote, Alessandra de Queiroz (2019)
This work measures the relative importance of aggregate and sectoral fluctuations on the dynamics of sectoral tax ICMS in the State of Ceará, from July 2007 to December 2016. In order to model the temporal dynamics of the tax collection segments dynamic factor model, the data was subdivided into segments with regulated prices (Fuel, Electric Energy, Communication and Transportation) and segments with free prices (Industry, Wholesale Trade, Retail Trade and Lodging and Food Services). The analyzes of variance decomposition and loading of factors indicated that fluctuations of regulated-prices segments are driven largely by idiosyncratic shocks, with low relative importance of the sectorial factor. To the segments with free prices, was observed a greater interdependence, as well as a greater relative importance of common fluctuations in the tax dynamics. In sum, it is suggested that the tax policies adopted for the regulated price segments are weakly integrated, so that the observed collection dynamics fluctuate in an uncoordinated way, reducing the capacity of the State to soften the fluctuations in the ICMS tax collection.